A Comparison of Three Monolingual Learner’s Dictionaries - Visutwarin, Thanasorn; Singhasiri, Wareesiri (rEFLections, 2007)
This study was conducted to examine similarities and differences among three monolingual learner’s dictionaries (MLDs). The selected MLDs, resulting from a survey of 200 first-year KMUTT students’ use of MLDs, were Oxford Student’s Dictionary of English (2001), Longman Active Study Dictionary (2004) and Macmillan Essential Dictionary (2003). To analyze for both macrostructure and microstructure, this study used Hartmann’s (2001) and Jackson’s (2002) criteria. For macrostructure, all three MLDs included basic essential components that good dictionaries should contain: use of defining vocabulary, language contents (collocation, grammar of words) and illustrations and a guide to the dictionary; however, only three minor items differed among the three dictionaries, viz. the introduction, the total number of entries and the content of reference sections. For microstructure, there were six elements which resemble each other: headwords, homonym numbers, illustrative sentences, word classes, pronunciations and miscellanea; however, there were two elements which differ from each other: how to organize frequently-used and polysemous words.